5 - Crystallising Commitment to Transformation in a South African Higher Education Institute - Helen M. Macdonald, (Journal of Higher Education in Africa, 2010)
This paper emerges out of an ethnographic study conducted at the University of Cape Town that explored the dynamics of an intervention providing a ‘safe space’ for university staff to engage in alternative ways with South Africa’s apartheid past, the university’s institutional culture and with each other. This paper focuses on the social politics that arose between the intervention, its participants and imagined non-participants in relation to the university’s ‘transformation’ vision. The interventionist intention was reworked by participants at a ground level into key symbols by which participants shaped the patterns of their behaviours and gave meaning to their experiences. Utilising Ortner’s (1973) model for recognising and using key symbols, I argue that ‘transformation’ and ‘safe space’ are elaborating symbols in that they have conceptual and action elaborating power. These elaborating symbols operate in relay with a kind of logic that ‘crystallises commitment’ from participants to the intervention in an emotionally powerful and relatively undifferentiated manner. In so doing, they render the intervention a ‘summarising’ symbol capable of expressing what their experience means to them as an imagined community in relation to others.